The Evolution and Impact of Furniture Design in Contemporary Society - Burcin Saltik (BioResources)
Furniture design has undergone a significant transformation over the centuries, evolving from purely functional objects to artistic expressions that reflect societal values, technological advancements, and environmental concerns. In contemporary society, furniture design plays a critical role not only in shaping interior spaces but also in influencing lifestyle, culture, and sustainability. The modern emphasis on minimalism, ergonomics, and multifunctionality reflects changing living patterns, urbanization, and an increased focus on well-being. Technological innovations, such as digital fabrication and smart materials, have further expanded the possibilities of design, enabling more personalized and efficient solutions. Additionally, there is a growing consciousness around sustainable practices, leading to the use of eco-friendly materials and circular design principles. This evolution highlights the intersection of aesthetics, utility, and ethics in modern design. By examining key trends and innovations, this study explores how contemporary furniture design responds to the needs of a dynamic society and contributes to shaping the future of living environments.